Use of the Nellix EVAS system to treat post-EVAR complications and to treat challenging infrarenal necks - Böckler, Dittmar; Reijnen, M. M. P. J.; Krievins, D.; Peters, Andreas; Hayes, P.; De Vries, J. P. (The journal of cardiovascular surgery, 2014)
AIM: Current commercially available modular stentgrafts are associated with relevant reintervention rates during follow-up. The Nellix Endovascular Aneurysm Sealing (EVAS) System is a potential device to overcome these limitations of EVAR. Device implantations outside of manufacturer instructions for use due to challenging neck anatomies are very common. This article presents very early experience in the treatment of patients with post EVAR complications and challenging neck anatomies. - METHODS: EVAS with the Nellix System consists of bilateral PTFE-covered stentgrafts surrounded by endobags which are filled with biostable polymer which cures after 3-5 minutes. The device and concept is designed to seal the entire aneurysm lumen, to withstand lateral displacement forces and effectively seal lumbar or inferior mesenteric arteries. Potentially, device migration, type II endoleak, and subsequent reinterventions will be reduced in the longterm. Single case experience in four European vascular centers is reported using Nellix off-IFU (instructions for use), addressing technical aspects as well as patient selection criterias. - RESULTS: Recent preliminary clinical experience using Nellix outide of the IFU in challenging neck anatomies prooves early feasibility and efficacy in patients being excluded for open repair (OR) and also for EVAR and FEVAR within OR. Short-term results are promising. Migration, renal artery occlusions or type II endoleaks were not observed. One type Ia endoleak was observed but was temporary and resolved. We also found that the chimney technique is feasible with Nellix, where secondary target vessel loss nor gutters were observed. The EVAS concept is a potential tool to treat post EVAR complications such as secondary type I endoleak or type IV material fatigue. Feasibility has been proven in single cases. - CONCLUSION: EVAS is an innovative, intriguing concept in the treatment of abdominal aortic aneurysm (AAA). Short-term outcomes of the Nellix system is promising. Early experience of Nellix out of IFU when treating patients with challenging proximal infraenal necks, with post EVAR complications, short necks and chimney techniques show technical feasibility and promising short-term results. Mid- and long-term data are needed to validate device and procedure durability.